Implikasi Hukum Perubahan Undang-Undang Penyelenggaraan Ibadah Haji dan Umrah: Telaah terhadap Legalitas Umrah Mandiri dan Pembentukan Kementerian - Sulistiawati Sulistiawati; Muh. Arbai Santoso; Adrian Bimantara; Chandra Evita; Agus Riyadi; Eko Purwanto; Firman Adi Candra (Institut Agama Islam Nasional Laa Roiba Bogor, 2026)
This article analyzes the review of Hajj and Umrah regulations in Indonesia, specifically Law Number 8 of 2019 and its recent revisions. This research aims to identify legal issues arising from the implementation and changes in regulations, and to examine their implications for pilgrim protection and the effectiveness of pilgrimage organization. Utilizing a literature study approach and regulatory analysis, this article will discuss legislative dynamics, including the legalization of independent Umrah and the establishment of a Ministry of Hajj and Umrah. The research findings are expected to provide a deep understanding of the current legal landscape of Hajj and Umrah and its future challenges.